The use of copper isotopes for understanding metal transfer mechanisms within the continuum mine-river-dam (Huelva Region, Spain) - Viers, Jérôme; Freydier, Rémi; Grande, Jose Antonio; Zouiten, Cyril; Marquet, Aurelie; Delpoux, Sophie; Santisteban, Maria; Pokrovsky, Oleg S.; Fortes, Juan Carlos; Davila, Jose Miguel; Sarmiento, Aguasante; Audry, Stéphane; et al. (Environmental science and pollution research)
Mining areas and in particular those containing massive sulfdes have left a heavy environmental legacy with soils and hydrographic networks highly contaminated with metals and metalloids as for example in the Iberian Pyrite Belt (Huelva, Spain). Here, we present new data on copper (Cu) isotopic composition of waters and solids collected along a continuum Mine (Tharsis)—River (Meca)—Lake (Sancho) in the Iberian Pyrite Belt. Our results show that the isotopic signature of pit lakes is spatially variable, but remains stable over the seasons; this signature seems to be controlled by water–rock interaction processes. The data obtained on the Meca River imply a number of attenuation processes such as decrease in the metal concentration by precipitation of secondary minerals. This is accompanied by preferential retention of the heavy isotope ( 65Cu) with a possibility of living organisms (e.g., algae) participation. The terminal Sancho lake demonstrated constant isotopic signature over the entire depth of the water column despite sizable variations in Cu concentrations, which can be tentatively explained by a superposition of counter-interacting biotic and abiotic processes of Cu fractionation. Overall, the understanding of the isotopic variations along the hydrological continuum is useful for a better understanding of metal element transfer within mining environments and surrounding surface waters.